Elementary Differential Equations and Boundary Value Problems 9th Edition

Published by Wiley
ISBN 10: 0-47038-334-8
ISBN 13: 978-0-47038-334-6

Chapter 3 - Second Order Linear Equations - 3.1 Homogenous Equations with Constant Coefficients - Problems - Page 144: 9



Work Step by Step

1) $$y''+y'-2y=0,\quad{y}(0)=1,\quad{y'}(0)=1$$Let $y-e^{\lambda{x}}$ so that $(\ln{y})'=\lambda$. $${\lambda}^2+{\lambda}-2=0$$ $$(\lambda-1)(\lambda+2)=0$$ $$\lambda_{1,2}=1,-2$$ The general solution is ${y}=c_{1}\exp^{x}+c_{2}\exp^{-2x}$. Substituting in the constraints, we obtain $c_{1}+c_{2}=1$ and $c_{1}-2c_{2}=1\rightarrow{c}_{1}+c_{2}=c_{1}-2c_{2}\rightarrow{c}_{2}=0\rightarrow{c}_{1}=1$. $$\therefore{y}=\exp^{x}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.